Carbon Nitride-Based Catalysts for High Pressure CO2 Photoreduction - Matteo Tommasi; Francesco Conte; Ilenia Rossetti; Gianguido Ramis (Materials Proceedings)
In this work we focus on carbon nitride materials to improve the conversion and productivity of the photoreduction of CO2, developing a coupled strategy to optimize materials and operating conditions. The metal-free polymeric catalyst, graphitic carbon nitride (g-C3N4), is a relatively novel material, characterized by a wide absorbance in the visible region and demonstrating a superior performance compared to the commercial titania P25 benchmark, the most used photocatalyst for this application. We used an innovative photoreactor operating at high pressures of up to 20 bar, which is unprecedented in photocatalytic applications where transparent windows are needed. This enabled a boost in the solubility of CO2 in water when operating the reactor as a tri-phase liquid/gas/solid device and improved the surface adsorption over the catalyst. The best productivity for HCOOH so far achieved with these catalysts at 8 bar, pH = 14 and by using Na2SO3 as a hole scavenger was ca. 370 g/h kgcat. Such productivity is several orders of magnitude higher than the literature values.